Asia and the Pacific basin: towards an integrated model of corruption: opportunities and control in China - Chan, Kin-man (2000)
This article uses a transaction costs approach to synthesize micro- and macro-theories of corruption in an analysis of corruption in post-Mao China. Macro-theories of corruption include functional, political-institutional, revised modernization, and cultural approaches. These approaches are integrated through a micro-model developed from the principal-agent model and a rational choice model of crime. The micro-model focuses on: the frequency of corrupt opportunities and the stakes involved, external control such as legal sanctions, and internal control or moral constraints. Within this context, this study reveals that corruption during the post-Mao China period was caused by the surge of such opportunities and the failure of internal and external control. - Reproduced
Keywords: Corruption - China; Corruption